2022
DOI: 10.37828/em.2022.51.9
|View full text |Cite
|
Sign up to set email alerts
|

Sperchon milisai nov. sp., an overlooked new species of water mites (Acari, Hydrachnidia, Sperchontidae) from Montenegro and Croatia, based on morphological and DNA barcode evidence

Abstract: In the present study a new species, Sperchon milisai sp. nov. is described from Montenegro and Croatia based on morphological and DNA barcoding data. Surprisingly, morphological evidence revealed that the new species is most similar to S. ampliscutatus Pešić & Smit, 2020, from Kyrgyzstan, confirmed by the phylogenetic analysis based on COI data. The average K2P-distance between DNA-barcode sequences of S. milisai sp. nov. and S. ampliscutatus was estimated at 15.51±1.6%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Cryptic diversity within the Skadar Lake area Due to the turbulent geological history of the Balkan Peninsula and Skadar Lake Lake itself (details in (Grabowski et al 2018)), the aquatic fauna of the basin is rich in endemics (Pešić andGlöer 2013, 2018;Jabłońska et al 2018Jabłońska et al , 2020. Most of the endemicity was detected in obligatory aquatic invertebrates (the whole life cycle in water), such as amphipods (Jabłońska et al 2020), shrimps (Jabłońska et al 2018), snails (Pešić andGlöer 2013, 2018;Pešić et al 2019), leeches (Grosser et al 2015;Marinković et al 2019;Jovanović et al 2021), and water mites (Pešić 2022;Pešić et al 2021aPešić et al , 2021bPešić and Smit 2020;). Recent morpho-molecular studies on Lake Skadar Chironomidae done by Gadawski et al (2022a) revealed the presence of new BINs, which could be identified only at the genus level.…”
Section: Species With High Intraspecific Variabilitymentioning
confidence: 99%
“…Cryptic diversity within the Skadar Lake area Due to the turbulent geological history of the Balkan Peninsula and Skadar Lake Lake itself (details in (Grabowski et al 2018)), the aquatic fauna of the basin is rich in endemics (Pešić andGlöer 2013, 2018;Jabłońska et al 2018Jabłońska et al , 2020. Most of the endemicity was detected in obligatory aquatic invertebrates (the whole life cycle in water), such as amphipods (Jabłońska et al 2020), shrimps (Jabłońska et al 2018), snails (Pešić andGlöer 2013, 2018;Pešić et al 2019), leeches (Grosser et al 2015;Marinković et al 2019;Jovanović et al 2021), and water mites (Pešić 2022;Pešić et al 2021aPešić et al , 2021bPešić and Smit 2020;). Recent morpho-molecular studies on Lake Skadar Chironomidae done by Gadawski et al (2022a) revealed the presence of new BINs, which could be identified only at the genus level.…”
Section: Species With High Intraspecific Variabilitymentioning
confidence: 99%